Dataset on microclimate and drone-based thermal patterns within an oil palm agroforestry system - Laura Somenguem Donfack; Alexander Röll; Florian Ellsäßer; Martin Ehbrecht; Bambang Irawan; Dirk Hölscher; Alexander Knohl; Holger Kreft; Eduard J. Siahaan; Leti Sundawati; Christian Stiegler; Zemp, Clara (My University, 2021)
Microclimate and Land Surface Temperature (LST) are important analytical variables used to understand complex oil palm agroforestry systems and their effects on biodiversity and ecosystem functions. In order to examine experimental effects of tree species richness (0, 1, 2, 3 or 6), plot size (25 m2, 100 m2, 400 m2, 1600 m2) and stand structural complexity on microclimate and Land Surface Temperature, related data were collected following a strict design. The experiment was carried out in the Jambi province, in Sumatra (Indonesia), as part of the collaborative project EFForTS [Ecological and Socioeconomic Functions of Tropical Lowland Rainforest Transformation Systems]. Microclimate data collected using miniaturized data loggers combined with drone-based thermal data were considered within an oil palm plantation enriched with six target tree species. The timeframe considered for data analysis was 20th September 2017 to 26th September 2017. The experiment data can be used for comparison with data from conventional oil palm agroforestry systems in the tropics. They can more specifically be used as reference to assess microclimate and Land Surface Temperature patterns within similar agroforestry systems.